2014
DOI: 10.1155/2014/371218
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Evaluation of Bioactive Metabolite from Endophytic Fungus, Aspergillus flavipes KF671231

Abstract: Of the total 40 endophytic fungi isolated from foliar tissues of medicinal plant Stevia rebaudiana Bertoni, a fungal isolate, Aspergillus flavipes, was subjected to bioassay guided fractionation. The fractionation was found active against medicinal plant pathogen Sclerotinia sclerotiorum with an inhibition zone of 29 mm in size. Further the metabolite was extracted which shows 20% growth inhibition in 24 h and 46% after 48 h, respectively. Bioassay guided chemical compound was identified as 1,2-benzenedicarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Mohammed et al [52] have focused their studies on the secondary metabolites produced by A. flavus and identified thirty one bioactive compounds in its methanolic extract such as aromatic rings, alkenes, aliphatic fluoro compounds, aromatic nitro compounds, ammonium ions and organic nitrate. In accordance, Verma et al [53] demonstrated that the ethyl acetate extract of A. flavipes, associated to the medicinal plant Stevia rebaudiana, displayed antifungal activity toward the soilborne fungus Scletotinia sclerotiorum. Total inhibition of Pythium ultimum growth was induced by extracellular metabolites of A. niger, A. terreus and A. flavus recovered from soil and compost teas [38].…”
Section: Discussionmentioning
confidence: 66%
“…Mohammed et al [52] have focused their studies on the secondary metabolites produced by A. flavus and identified thirty one bioactive compounds in its methanolic extract such as aromatic rings, alkenes, aliphatic fluoro compounds, aromatic nitro compounds, ammonium ions and organic nitrate. In accordance, Verma et al [53] demonstrated that the ethyl acetate extract of A. flavipes, associated to the medicinal plant Stevia rebaudiana, displayed antifungal activity toward the soilborne fungus Scletotinia sclerotiorum. Total inhibition of Pythium ultimum growth was induced by extracellular metabolites of A. niger, A. terreus and A. flavus recovered from soil and compost teas [38].…”
Section: Discussionmentioning
confidence: 66%
“…Lastly, 1,2-benzene dicarboxylic acid, mono 2-ethylhexyl ester (7) has been detected in various sources ranging from plant extracts (Akpuaka et al, 2012 ; Sivasubramanian and Brindha, 2013 ), endophytic fungal (Verma et al, 2014 ), and also microbial origin including Streptomyces sp. (Krishnan et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we observed that A. unguis AG 1.1 (G) ethyl acetate extract demonstrated antimicrobial activity against Gram negative bacterial pathogens, E. coli, P. aeruginosa, and X. campestris (Kamat et al, 2020). A high concentration of 1,2-benzene dicarboxylic acid mono(2-ethylhexyl) ester contributed to the antifungal activity of the endophytic fungi, Aspergillus flavipes strain (Verma et al, 2014). Many pathogenic fungi have the ability to produce prostaglandins that act as virulence factors (Noverr et al, 2002).…”
Section: Discussionmentioning
confidence: 97%